Theoretical energies, transition rates, lifetimes, hyperfine interaction constants and Lande´ gJ-factors for the Se XXVII spectrum of fusion interest. (February 2018) - Chen, Zhan-Bin; Guo, Xue-Ling; Wang, Kai
Highlights: Energies, transition rates, hyperfine interaction constants, and Landé gJ -factors for the lowest 318 levels for the Se XXVII spectrum of fusion interest are reported. The most accurate and complete, as of today, atomic data on Se XXVII are provided. Abstract: An extensive set of level energies, wavelengths, line strengths, oscillator strengths, lifetimes, hyperfine structures, Land e ´ g J -factors, electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2), and magnetic quadrupole (M2) radiative transition rates among the lowest 318 states arising from the 2s 2 2p 4, 2s2p 5, 2p 6, 2s 2 2p 3 3 l ( l = 0, 1, 2), 2s2p 4 3 l ( l = 0, 1, 2), 2p 5 3 l ( l = 0, 1, 2), and 2s 2 2p 3 4 l ( l = 0, 1, 2, 3) configurations has been obtained for Se XXVII. These new data, calculated within the frameworks of the multi-configuration Dirac–Hartree–Fock method and the second-order many-body perturbation theory, fill in the gap existing in the atomic data needed for the diagnostic processes of tokamak plasmas. Using two methods allowed us to make an intercomparison and to estimate the uncertainties on the obtained data. The results arising in the two sets of calculations are quite close, suggesting that there is a high degree of convergence achieved in our work. i.e., our two sets of energies agree to better than 0.02%, and the lifetimes mostly agree to within 2%. Comparison is also made with the limited number of experimental data and previous computations to assess the accuracy of our calculations.